Mediators of glucagon-like peptide 2-induced blood flow: Responses in different vascular sites - KURTEL, HIZIR (ELSEVIER SCIENCE BV, 2007)
The aims of the present study were: to characterize the mechanisms of hemodynamic alterations induced by GLP-2, and, to compare the responses elicited in the superior mesenteric artery (SMA) to other vascular beds. Anesthetized rats were infused at the doses of 0.9, 2.3, 4.6 and 9.3 nmol/kg into the jugular vein for 60 min. Blood flow in the various arteries was measured by the ultrasonic transit time technique. Some animals were pretreated with indomethacin (5 mg/kg, ip), L-NAME (9, 18, 36 and 72 mu mol/kg, iv), atropine sulfate (1-2 mg/kg, iv), CCK-1 and CCK-2 receptor antagonists (L-364,718 and L-365,260, 1 mg/kg, iv), exendin (9-39) amide (35 nmol/kg, iv) and lidocaine (74 mu mol/kg, iv) prior to the infusion of GLP-2 (4.6 nmol/kg). In another group, capsaicin was applied either systematically (125 mg/kg, sc) or vagally (1 mg/rat). GLP-2 administration at all doses significantly increased the SMA blood flow throughout the experiments. GLP-2 (4.6 nmol/kg) infusion significantly increased blood flow of inferior mesenteric artery and carotid artery but not in any other vessel measured. Only the pretreatments With L-NAME and lidocaine were ineffective in preventing the GLP-2-induced responses. These results implicate that GLP-2-induced blood flow alterations are most significant in the SMA and are not mediated by prostaglandins, muscarinic, GLP-1 or CCK receptors. Our results also suggest that the stimulatory effect of GLP-2 on SMA blood flow is NO-dependent and mediated via intrinsic, non-cholinergic enteric neurons. (c) 2007 Published by Elsevier B.V
Keywords: GLP-2; blood flow; small intestine; MONOMETHYL-L-ARGININE; NITRIC-OXIDE; SENSORY NEURONS; NERVOUS-SYSTEM; SUBSTANCE-P; ESSENTIAL-HYPERTENSION; EXPERIMENTAL COLITIS; ABSORPTIVE FUNCTION; GUINEA-PIGS; LIDOCAINE